The Application of Instagram Social Media to Qualitative Analysis Materials for Groups I and II to Increase Student Interest in Learning - Deni Ainur Rokhim; Hayuni Retno Widarti; Munzil Munzil; Neena Zakia (Postgraduate, University of Mataram, 2022)
This study aims to determine the effectiveness of the application of Instagram media on students' interest in learning group I and II cation analysis materials. The data collection method used qualitative analysis with a descriptive approach. The results of the media validation get an average score of 84.27%, so the media is very feasible to be used in this study. Respondents in this study were students who followed the @kimiafun2022 Instagram account and interacted in answering questions and responses on Instagram. The study results show that the Instagram application can effectively increase student interest in learning about group I and II cation analysis materials, which is considered problematic